Effect of Vitamin D Supplementation on Risk of Breast Cancer: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Li, Ziyi; Wu, Liangzhi; Zhang, Junguo; Huang, Xin; Thabane, Lehana; Li, Guowei (Frontiers in Nutrition, 2021)
Objective: Laboratory findings indicated that vitamin D might have potent protective effect on breast cancer, but epidemiology studies reported conflicting results. The aim of the study was to conduct a systematic review and meta-analysis to clarify the efficacy of vitamin D supplementation on risk of breast cancer. Methods：MEDLINE, EMBASE, The Cochrane Central Register of Controlled Trials, ClinicalTrials.gov and abstracts of three major conferences were searched (up to December 8th, 2020). Parallel randomized controlled trials (RCTs) examining the efficacy of vitamin D supplementation on risk of breast cancer or change of mammography compared with placebo in females were included. Data were meta-analyzed using a random-effects model. Bayesian meta-analysis was conducted to synthesize the results using data from observational studies as priors. Results: Seven RCTs were identified for effect of vitamin D on risk of breast cancer, with 19,137 females included for meta-analysis. No statistically significant effect of vitamin D on risk of breast cancer was found in classical random-effect meta-analysis (Risk Ratio = 1.04, 95% Confidence Interval: 0.84 to 1.28, p = 0.71). When Bayesian meta-analyses were conducted, results remained non-significant. There was no statistically significant effect of vitamin D on mammography density observed: Mean difference = 0.46, 95% Confidence Interval: -2.06 to 2.98, p = 0.72. Conclusion: There is insufficient evidence to support the efficacy of vitamin D supplementation in breast cancer risk and change of mammography density. Protective effect of vitamin D on risk of breast cancer from previous observational studies may be overestimated. Registration: PROSPERO (identifier: CRD42019138718).